Effects of fire history on animal communities: a systematic review - González, Tania Marisol; González-Trujillo, Juan David; Muñoz, Alberto; Armenteras, Dolors (Ecological processes, 2022)
Fire is a natural agent with a paramount role in ecosystem functioning and biodiversity maintenance. Still, it can also act as a negative force against many ecosystems. Despite some knowledge of the interactions of fire and vegetation, there is no clear understanding of how different components of fire regimes (i.e., severity, history, or frequency) influence known patterns of animal communities. Therefore, we performed a systematic review on the global responses of arthropods, birds, mammals, reptiles, and amphibians to different fire regimes. Specifically, we focused on assessing how fire severity, history, and frequency modulate the effect of fire on the richness and abundance of faunal communities. We conducted a systematic review of 566 papers retrieved from the Scopus database. We also scrutinized all the documents included in the meta-analysis of Pastro et al. (Pastro et al. Glob Ecol Biogeogr 23:1146–1156, 2014). Our selection criteria excluded studies without data on species richness or abundance. We also excluded studies without adequate controls and those without information about the fire regime of the study zone. After careful examination, we used data from 162 studies to perform a quantitative meta-analysis. From the 162 studies meeting our selection criteria, nearly 60% of the studies are from North America, 25% from Australia, 11% from Europe, and 4% from the tropics. According to the ecological role of fire, 90% of the studies were carried out in fire-dependent ecosystems (i.e., conifer forests, natural savannas, pastures). Finally, 40% of the studies analyzed birds, 22% mammals, and 20% arthropods. The meta-analysis of the available evidence indicates that fire history is an important modulator of animal richness and abundance. Whether negative or positive, animal responses depended on the time since the last fire event. Considering that short-term studies may not capture such a long-term effect on fauna, this translates to more challenges at implementing fire management strategies. Whether or not we can anticipate the impact of the fire will then depend on future efforts to implement long-term research.